From Qur’anic Normative Understanding to Institutional Practice: Zakat, Infaq, and Sadaqah Management at Baznas Batu Bara Regency - Rini Angraini; Farhan Indra (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2026)
This study examines how Qur’anic verses on zakat, infaq, and sadaqah are understood and operationalized in the institutional practices of BAZNAS Batu Bara Regency, Indonesia. While previous studies have largely discussed zakat effectiveness, productive zakat, zakat literacy, and the impact of Islamic philanthropy on mustahik welfare, limited attention has been given to how regional zakat institutions translate Qur’anic normative understanding into program governance. This study employed a qualitative case study design. Data were collected through interviews with BAZNAS administrators, a community figure, and mustahik beneficiaries, supported by limited observation and institutional documentation. The findings show that QS. At-Taubah [9]:103 is understood as a basis for the purification of wealth and the self, QS. At-Taubah [9]:60 as a framework for distributive justice through the eight asnaf, and QS. Al-Baqarah [2]:261 as a foundation for continuing social benefit. These values are reflected in several programs, including Batu Bara Sejahtera, Batu Bara Cerdas, Batu Bara Sehat, Batu Bara Peduli, Batu Bara Taqwa, and Kampung Zakat. However, the translation of Qur’anic values into measurable operational mechanisms remains limited, particularly in beneficiary verification, assistance records, distribution frequency, mentoring, monitoring, and evaluation of mustahik change. The study concludes that Qur’anic values shape the general orientation of BAZNAS Batu Bara programs, but stronger institutional governance is needed to transform these values into transparent, accountable, and evaluable ZIS management. The findings contribute to Islamic philanthropy studies by identifying both the connection and the gap between religious normative understanding and institutional zakat governance at the regional level.